Improving the Competence of Elementary School Teachers Through Assistance in the Preparation of Numeracy-Based Literacy Teaching Modules - Dwi Cahaya Nurani; Laihat; Vina Amilia Suganda M; Mazda Leva Okta Safitri; Marwan Pulungan; Najlatul Fathia; Fahmi Surya Adikara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The curriculum continues to change, and until now Indonesia has been implementing the curriculum.The teacher's ability to implement the curriculum will be a benchmark for his success in implementing the current curriculum. Literacy culture is still a hot topic to discuss. Unfortunately, in Indonesia, the culture of literacy is still low and has not yet become a social culture. To be able to keep up with the times, students must have basic abilities, namely literacy and numeracy. Literacy and numeracy learning in elementary schools must be carried out through innovative learning activities so that it can increase students' interest in learning, as well as develop elementary school students' literacy and numeracy skills. Based on the results of a preliminary study by the Community Service team in Lahat Regency through the results of initial interviews with the education office and several elementary school teachers, information was obtained that teachers were not yet skilled in developing teaching modules related to literacy and numeracy for elementary school students. In connection with this problem, it is necessary to provide an alternative solution, one of which is training related to literacy and numeracy-based module design. After participating in the training, it is hoped that elementary school teachers in Lahat Regency can easily develop literacy and numeracy-based teaching modules so that the quality of learning in the classroom becomes higher, which will have an impact on student learning outcomes. The method used in this community service is counseling and guidance, which is carried out online and offline. In the results of the pretest before being given assistance, participants got an average score of 41, and after being given assistance, the post-test score of participants got an average score of 70.7. Assistance in the development of literacy and numeracy-based teaching modules for elementary school teachers in Lahat district went smoothly, as demonstrated by the teachers' success in designing appropriate teaching modules, and there was an increase in the pretest and post-test scores that had been given.